ENHANCING MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHER EDUCATION IMPROVES THE QUALITY OF EDUCATION AND RESEARCH (European Journal of Emerging Technology and Discoveries, 2024)
The objective of this article is to present an analysis of contemporary pedagogical technologies and their implications for the field of teacher education. It also examines the significance of pedagogical technologies in the contemporary digital era, which facilitate access to education and training for both students and instructors. The article emphasizes the role of online platforms in facilitating the academic progress and knowledge acquisition of both students and instructors. Aspects of contemporary pedagogical technologies that may have an effect on the teaching and learning process are investigated in this study. It proposes the incorporation of contemporary pedagogical technologies into Uzbek universities and schools.